The relationship between insomnia symptoms and the dark triad personality traits. (1st September 2018) - Akram, Umair; Allen, Sarah; McCarty, Kristofor; Gardani, Maria; Tan, Alice; Villarreal, Daniel; Bilsborough, Emily; Dooher, Grace; Gibbs, Grace; Hudson, Jess L.; Mills, Rachel; Subramaniam, Viknesh; et al.
Abstract: This study examined the relationship between the dark triad personality traits and insomnia symptoms amongst a sample of the general-population. Four hundred and seventy-five individuals completed online measures of dark triad personality traits (SD3) and insomnia severity. Symptoms of insomnia were independently related to Machiavellianism and psychopathy, but not narcissism in univariate analyses. Moreover, linear regression analysis determined that psychopathy and sex, but not Machiavellianism, significantly predicted insomnia symptoms. These outcomes contribute to the limited research examining the dark triad personality traits in relation to symptoms of insomnia. The disturbed sleep presented amongst those high in psychopathy may be due to deficits in emotion regulation which serve to accentuate maintaining factors of insomnia (i.e. negatively toned cognitive activity).